To find which expression for \( A \) makes the equation \( A = 5 - \frac{11}{3} \) true, we first need to simplify the right side of the equation.
- Calculate \( 5 - \frac{11}{3} \).
- Convert \( 5 \) into a fraction with a denominator of \( 3 \): \[ 5 = \frac{15}{3} \]
- Now perform the subtraction: \[ 5 - \frac{11}{3} = \frac{15}{3} - \frac{11}{3} = \frac{15 - 11}{3} = \frac{4}{3} \]
So, we have: \[ A = \frac{4}{3} \]
Next, let's convert \( \frac{4}{3} \) into a mixed number: \[ \frac{4}{3} = 1 \frac{1}{3} \]
Now, we will evaluate each expression for \( A \):
-
\( A = 1 \frac{2}{3} + 13 \):
- Convert \( 1 \frac{2}{3} \): \[ 1 \frac{2}{3} = \frac{5}{3} \]
- Now, add \( 13 \): \[ \frac{5}{3} + 13 = \frac{5}{3} + \frac{39}{3} = \frac{44}{3} \]
- This does not equal \( \frac{4}{3} \).
-
\( A = 1 \frac{2}{3} - 13 \):
- Continue with \( \frac{5}{3} \): \[ \frac{5}{3} - 13 = \frac{5}{3} - \frac{39}{3} = \frac{5 - 39}{3} = \frac{-34}{3} \]
- This does not equal \( \frac{4}{3} \).
-
\( A = 1 \frac{5}{3} + 13 \):
- Convert \( 1 \frac{5}{3} \): \[ 1 \frac{5}{3} = \frac{8}{3} \]
- Now, add \( 13 \): \[ \frac{8}{3} + 13 = \frac{8}{3} + \frac{39}{3} = \frac{47}{3} \]
- This does not equal \( \frac{4}{3} \).
-
\( A = -1 \frac{2}{3} + 13 \):
- Convert \( -1 \frac{2}{3} \): \[ -1 \frac{2}{3} = -\frac{5}{3} \]
- Now, add \( 13 \): \[ -\frac{5}{3} + 13 = -\frac{5}{3} + \frac{39}{3} = \frac{34}{3} \]
- This does not equal \( \frac{4}{3} \).
None of the expressions for \( A \) resulted in \( \frac{4}{3} \). There might have been a misunderstanding with the expressions. To find a mix of a fraction or integer equivalent to \( A = 1 \frac{1}{3} \) from the given expressions, you can review or adjust that list based on specified values.